2015
DOI: 10.21149/spm.v57i6.7637
|View full text |Cite
|
Sign up to set email alerts
|

End-of-life decisions in perinatal care. A view from health-care providers

Abstract: Grether P, Lisker R, Loria A, Álvarez-del Río A. ResumenObjetivo. Explorar la opinión del equipo de salud sobre las decisiones relacionadas con la atención de fetos y neonatos gravemente enfermos. Material y métodos. Se aplicó un cuestionario anónimo a médicos, trabajadoras sociales y enfermeras perinatales. Las diferencias se evaluaron con las pruebas chi cuadrada y t de Student. Resultados. Al tratar fetos y neonatos gravemente enfermos, 82 y 93% de los participantes optaron, respectivamente, por atención p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This article is protected by copyright. All rights reserved decision (24), or TOP indication (19,20,22,23,(25)(26)(27) and usually indicate large differences between study groups. Insight into attitudes of other healthcare professionals involve in late TOP decision-making and counselling, combined with personal influencing factors and a more detailed investigation according to severity or specific case, is lacking.…”
Section: Accepted Articlementioning
confidence: 99%
“…This article is protected by copyright. All rights reserved decision (24), or TOP indication (19,20,22,23,(25)(26)(27) and usually indicate large differences between study groups. Insight into attitudes of other healthcare professionals involve in late TOP decision-making and counselling, combined with personal influencing factors and a more detailed investigation according to severity or specific case, is lacking.…”
Section: Accepted Articlementioning
confidence: 99%
“…Moreover, due to differences in national legislations, international uniformity (of consensus) is difficult to reach. [3][4][5] Internationally, legislation on TOP varies strongly, [6][7][8][9] ranging from completely legal for any type of abortion regardless of pregnancy duration to TOP being allowed depending on certain preconditions such as pregnancy duration and presence of lethal foetal anomalies. 10 The Belgian abortion law is summarised in Box 1.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17] Previous studies showed that attitudes of healthcare providers towards TOP are influenced by personal obstetric history, 18 professional experience, [18][19][20] religious beliefs [18][19][20] and professional orientation, [20][21][22][23] eg maternal-fetal medicine specialists vs neonatal specialists, or doctors vs nurses. These studies are limited to studying physicians' or nurses' attitudes towards late TOP, or compare only one aspect, such as demographic factors, [18][19][20][21][22][23] the type of end-of life decision, 24 or TOP indication 19,20,22,23,[25][26][27] and usually indicate large differences between study groups. Insight into attitudes of other healthcare professionals involved in late TOP decision-making and counseling, combined with personal influencing factors and a more detailed investigation according to severity or specific case, is lacking.…”
Section: Introductionmentioning
confidence: 99%